2011
DOI: 10.1002/pen.22159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphate and polysiloxane on flame retardancy and impact toughening behavior of poly(2,6‐dimethyl‐1,4‐phenylene oxide)

Abstract: Poly(2,6-dimethyl-1,4-phenylene oxide) (PPO)-based compounds containing resorcinol bis(diphenyl phosphate) (RDP) and poly(dimethyl-diphenyl siloxane) (PDMDPS) were prepared through melt extrusion, and their flammability characteristics and mechanical properties were evaluated. The incorporation of RDP enhanced the flame retardancy of PPO compounds, but hardly made them obtain the UL 94 V-0 rating unless RDP and PDMDPS were combined. Studies on the residual chars after vertical burning test suggested that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Additives containing phosphorus flame retardants can promote carbonaceous char and inorganic residue formation on the polymer surface to inhibit the polymer surface from heat and air in condensed phase and inhibit flame spread due to radical trapping in gas phase. Among them, aryl phosphates, notably bisphenol A bis (diphenyl) phosphate ester (BDP), 8,9 resorcinol bis(diphenyl phosphate) (RDP), 13 and triphenyl phosphate (TPP), were found to be effective flame retardants in SEBS-based TPE (TPE-S). Aryl phosphates usually act like acid precursors and the produced acids join the charring through esterification and dehydration with polymer and other additives.…”
Section: Introductionmentioning
confidence: 99%
“…Additives containing phosphorus flame retardants can promote carbonaceous char and inorganic residue formation on the polymer surface to inhibit the polymer surface from heat and air in condensed phase and inhibit flame spread due to radical trapping in gas phase. Among them, aryl phosphates, notably bisphenol A bis (diphenyl) phosphate ester (BDP), 8,9 resorcinol bis(diphenyl phosphate) (RDP), 13 and triphenyl phosphate (TPP), were found to be effective flame retardants in SEBS-based TPE (TPE-S). Aryl phosphates usually act like acid precursors and the produced acids join the charring through esterification and dehydration with polymer and other additives.…”
Section: Introductionmentioning
confidence: 99%
“…PPO/HIPS‐0 with 9 wt% RDP and 3 wt% AP presented an increased LOI value of 31.5%, suggesting that RDP and AP was the efficient external flame retardant. It was reported that RDP could produce phosphorus‐containing compounds to promote the carbon formation of PPO, which was benefited for stabilizing the degradation products, and improving the quality of the char layer 31 . In contrast, the pure HIPS was highly combustible with an LOI value of just 18.5%.…”
Section: Resultsmentioning
confidence: 99%